Latinos in the new millennium : an almanac of opinion, behavior, and policy preferences - Fraga, Luis Ricardo (Cambridge University Press, 2012)
"Latinos in the New Millennium provides essential knowledge about Latinos in the United States, contextualizing research data by structuring discussion around dimensions of Latino political life in the U.S"--Provided by publisher